MANAGEMENT MODELS IN INDOOR SPORTS FACILITIES - Vitali, Rodrigo Oliveira (LUMEN ET VIRTUS, 2024)
The topic of management of indoor sports facilities has gained prominence in Brazil, especially due to the growing demand for spaces that combine structural quality, financial sustainability and potential for social inclusion. This work explored how different management models have been implemented in these environments, pointing out advances and weaknesses that directly affect the efficiency and relevance of these structures in the daily lives of communities. The research brought together academic publications that deal with strategic planning, use of monitoring technologies, institutional marketing practices, preventive maintenance processes and strategies to diversify funding sources. It was evident that, although there are positive experiences marked by the professionalization of teams and the use of performance indicators, it is still common to lack integrated long-term policies that ensure the modernization of spaces and the continuous supply of quality services. It was also found that factors such as accessibility, environmental sustainability and social participation continue to be important challenges to be faced by managers. By highlighting these issues, the study contributes to broadening the debate on how to make indoor sports centers more prepared to meet increasingly complex and diverse demands, proposing reflections that can inspire public policies and innovative management practices.